Visualizing semantic analysis of text data with time and importance through an interactive exploratory system - Ho, Jaejong; Gong, Hyeonsik; Lee, Kyungwon (International Conference on Intelligent User Interfaces, Proceedings IUI, 2020)
The main purpose of this visualization is for developing a visualization system to help users navigate their text data so that users can easily identify the main topics of data. In addition, the visualization system allows users to set options, such as text data processing pipelines, or provides proper interactions, giving them more flexible and diverse user experience of viewing data. Users are able to identify topic keywords and the distribution of clustered text data with a hexagonal view. They can zoom the view for detailed topic of the data distribution. Also, after dragging areas or selecting internal hexagons, they cannot only grasp the topic change over time of the selected data, but can also understand the relationship between the topic keywords. Furthermore, they can compare the main keywords by each cluster of selected data.
Keywords: Data distribution; NAtural language processing; Semantic analysis; Text data; Visualization system; Data Visualization; HCI; Natural Language Processing